2013
DOI: 10.1037/a0031111
|View full text |Cite
|
Sign up to set email alerts
|

The development of pointing perception in infancy: Effects of communicative signals on covert shifts of attention.

Abstract: The present study aims to investigate the interplay of verbal and nonverbal communication with respect to infants' perception of pointing gestures. Infants were presented with still images of pointing hands (cue) in combination with an acoustic stimulus. The communicative content of this acoustic stimulus was varied from being human and communicative to artificial. Saccadic reaction times (SRTs) from the cue to a peripheral target were measured as an indicator of the modulation of covert attention. A significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
55
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 69 publications
(107 reference statements)
3
55
1
Order By: Relevance
“…Although these results converge with those reported by Rohlfing et al (2012) to suggest that infants orient in the direction of a pointing hand by 4 months of age, Daum et al (2013) suggest that infants do not orient in the direction of a pointing hand until 12 months of age. How can we reconcile these seemingly significant age differences?…”
Section: Point Following Versus Point Comprehensioncontrasting
confidence: 58%
See 3 more Smart Citations
“…Although these results converge with those reported by Rohlfing et al (2012) to suggest that infants orient in the direction of a pointing hand by 4 months of age, Daum et al (2013) suggest that infants do not orient in the direction of a pointing hand until 12 months of age. How can we reconcile these seemingly significant age differences?…”
Section: Point Following Versus Point Comprehensioncontrasting
confidence: 58%
“…It was sufficient for them to follow the direction of the point without any interpretation of its meaning. By contrast, infants in the Daum et al (2013) study were shown a pointing hand with an accompanying speech act. The combination of the two stimuli together may have resulted in infants interpreting the stimulus not as a directional cue, per se, but rather as a communicative act requiring that infants understand the referential intention of the pointing hand (i.e., infants appreciate that the hand is attached to a social partner who is directing their attention to a specific referent).…”
Section: Point Following Versus Point Comprehensionmentioning
confidence: 92%
See 2 more Smart Citations
“…These results were 302 GAMPE & DAUM extended by a further condition in which infants at the age of 10 months heard two labels that were unrelated to the visual category. The presence or absence of communicative speech has a substantial influence on infants' performance in an A-not-B error task at the age of 10 months (Top al, Gergely, Mikl osi, Erd€ ohegyi, & Csibra, 2008) and on the perception of pointing gestures at the age of 12 months (Daum, Ulber, & Gredeb€ ack, 2013). And even beyond the preverbal months, language can influence the way we perceive objects.…”
mentioning
confidence: 99%